Formation and Dissolution of Twin ZnO Nanostructures Promoted by Water and Control over Their Emitting Properties. Issue 26 (14th May 2014) - Distaso, Monica; Mačković, Mirza; Spiecker, Erdmann; Peukert, Wolfgang
Abstract By using ZnO as a model system, the formation of twinned nanostructures has been investigated under microwave irradiation, exploiting experimental conditions ranging from purely solvothermal when N, N‐dimethylformamide was used, to purely hydrothermal when water was the solvent. A progressive increase in size, elongation and roughness of the surface was observed with increasing water content in the solvent mixture. Particular attention was paid to the reactivity of the ZnO surfaces towards dissolution. Our results show that the formation of twinned nanorods is a dynamic process and that the coupling interphase itself is highly reactive. Consequently, the twinned rods undergo a number of complex dissolution processes that are responsible for the appearance of a wide distribution of defects either on the surface or inside the structure. Poly(N‐vinyl pyrrolidone) influences the photoluminescent properties of the as‐synthesised materials and allows control of the ratio of the intensity of the UV and visible emission.